EFFECTS OF VIRGIN COCONUT OIL SUPPLEMENTATION ON BIOMARKERS OF OXIDATIVE STRESS IN OBESE ADOLESCENTS - Suryani; Darius El Febrian; Fitratur Rahmah Agustina; Fitria Mushollini; Diana Angraini; Samnil Astuti Fitri; Aprilya Roza Werdani; Donal Ortega; Ahmad Faridi (JURNAL KATALISATOR, 2026)
Obesity in adolescents is a health problem whose prevalence is closely related to increased oxidative stress. Obesity conditions lead to increased production of reactive oxygen species (ROS) which can trigger lipid peroxidation, cell damage, and various metabolic disorders. Biomarkers of oxidative stress, such as malondialdehyde (MDA) levels and the activity of antioxidant enzymes, namely superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT), can be used to assess oxidative stress levels in obese individuals. Virgin Coconut Oil (VCO) is a functional food that contains medium-chain fatty acids (medium-chain triglycerides; MCTs) and phenolic compounds that are thought to have antioxidant and anti-inflammatory activity. The study aimed to analyze the effect of Virgin Coconut Oil supplementation on biomarkers of oxidative stress in obese adolescents. This study uses a quasi-experimental pretest-posttest control group design. A total of 40 obese adolescents aged 15–18 years were divided into two groups, namely the treatment group that received VCO supplementation of 15 mL per day for 8 weeks and the control group that received only balanced nutrition education. The results indicate that VCO supplementation has the potential to increase the body's antioxidant capacity and reduce oxidative stress in obese adolescents. Although the decrease in BMI and waist circumference did not show a statistically significant difference, there was a tendency to improve the anthropometric profile in the group receiving VCO